PERWATAKAN PROTAGONIS TOKOH ZAHRANA DALAM NOVEL CINTA SUCI ZAHRANA KARYA HABIBURRAHMAN EL-SHIRAZY - Sumiharti Sumiharti; Nila Kastri (Universitas Batanghari, 2021)
The purpose of this study was to describe the protagonist's character Zahrana in Habiburrahman El-Shirazy's Novel of Cinta Suci Zahrana. The protagonist of Zahrana in Habiburrahman El-Shirazy's novel Cinta Suci Zahrana is honest, humble, clever, and independent. This research falls into the qualitative descriptive. Qualitative descriptive research is a type of money research used to understand the phenomena experienced by subjects by describing words and language using data from research results in a novel. The data in the novel is in the form of quotations from aspects of the protagonist's character in character Zahrana contained in the novel Cinta Suci Zahrana by Habiburrahman El-Shirazy. The result of this study is a description of the aspects of the protagonist character of the character Zahrana in the novel Cinta Suci Zahrana by Habiburrahman El-Shirazy. Quotes about the protagonist's character are depicted in the character of Zahrana, which includes honest, humble, clever, and independent. As for the quotes depicting Zahrana has an honest personality, as many as 21 quotes, quotes that describe humble as many as 34 quotes, quotes that describe clever as many as 21 quotes. Self-described quotes as many as 12 citations with the number of sources obtained peer to 88 citations. Keywords: literary work, novel, protagonist character